2009
DOI: 10.1186/1471-2393-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Making stillbirths count, making numbers talk - Issues in data collection for stillbirths

Abstract: BackgroundStillbirths need to count. They constitute the majority of the world's perinatal deaths and yet, they are largely invisible. Simply counting stillbirths is only the first step in analysis and prevention. From a public health perspective, there is a need for information on timing and circumstances of death, associated conditions and underlying causes, and availability and quality of care. This information will guide efforts to prevent stillbirths and improve quality of care.DiscussionIn this report, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
130
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 76 publications
5
130
0
Order By: Relevance
“…Accurately counting will provide an opportunity to set specific goals, the first step towards any improvement. 1 In a study on underreporting of pertussis cases it was observed that diffused responsibility of reporting among different personnel and absence of proper definition for the disease to be reported, manual processes of data entry combined with knowledge deficits, contribute to problems with underreporting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurately counting will provide an opportunity to set specific goals, the first step towards any improvement. 1 In a study on underreporting of pertussis cases it was observed that diffused responsibility of reporting among different personnel and absence of proper definition for the disease to be reported, manual processes of data entry combined with knowledge deficits, contribute to problems with underreporting.…”
Section: Discussionmentioning
confidence: 99%
“…16 Failure to adhere to WHO definitions hampers stillbirth epidemiology. 1 In the present study only 59.64% of stillbirth had data on birth weight and sex in stillbirth register, data on rest of the stillbirth could be included in the study just because the data was available in the case sheet. Data on macerated vs. fresh was not available both on case sheet and the register for any of the stillbirth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vital registration data, when collected and reported by gestational age or birthweight alone, underestimated the stillbirth rate in Norwegian and Australian historical data for stillbirths at 22 weeks and older or 500 g birthweight and more by 19-30%, although in Norway once the stillbirth rate was less than fi ve per 1000 total births, the under-reporting was reduced to about 10%. 26 Thus, vital registration data cannot be thought of as an unalloyed gold standard. Comparison of the estimated trends with reported trends by country suggests that the current model's accuracy of predicting trends is close to that of the actual reported trends.…”
Section: Discussionmentioning
confidence: 99%
“…It also reflects the quality of antenatal care and obstetric management during labor and childbirth. 5,6 A stillbirth is emotionally devastating for the patients and the clinicians and many of these are preventable. Most often, the cause of the stillbirth cannot be identified.…”
Section: Introductionmentioning
confidence: 99%